The Transcription Factor PfAP2-O Influences Virulence Gene Transcription and Sexual Development in Plasmodium falciparum - Cubillos, Eliana F. G.; Prata, Isadora Oliveira; Fotoran, Wesley Luzetti; Ranford-Cartwright, Lisa; Wunderlich, Gerhard (Frontiers in Cellular and Infection Microbiology, 2021)
The human malaria parasite Plasmodium falciparum expresses variant PfEMP1 proteins on the infected erythrocyte, which function as ligands for endothelial receptors in capillary vessels, leading to erythrocyte sequestration and severe malaria. The factors that orchestrate the mono-allelic expression of the 45-90 PfEMP1-encoding var genes within each parasite genome are still not fully identified. Here, we show that the transcription factor PfAP2-O influences the transcription of var genes. The temporary knockdown of PfAP2-O leads to a complete loss of var transcriptional memory and a decrease in cytoadherence in CD36 adherent parasites. AP2-O-knocked down parasites exhibited also significant reductions in transmission through Anopheles mosquitoes. We propose that PfAP2-O is beside its role in transmission stages also one of the virulence gene transcriptional regulators and may therefore be exploited as an important target to disrupt severe malaria and block parasite transmission.